2016
DOI: 10.1016/j.watres.2015.10.026
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the transformation of trimethoprim during biological wastewater treatment

Abstract: The antibiotic trimethoprim (TMP), a micropollutant found at μg/L levels in raw wastewater, was investigated with regard to its (bio)transformation during biological wastewater treatment. A pilot-scale, nitrifying/denitrifying Sequencing Batch Reactor (SBR) fed with municipal wastewater was monitored for TMP removal during a 16-month monitoring study. Laboratory-scaled bioreactors spiked with TMP were applied to identify the transformation products (TPs). In total, six TPs could be identified from TMP. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 30 publications
4
67
2
Order By: Relevance
“…NOBs were representing less than 0.1% (mostly Candidatus Nitrotoga arctica ) of the community. These results can explain the differences in the negative effect of antibiotics on nitrifying community between this study and previously reported data because of different key nitrifying bacteria …”
Section: Resultssupporting
confidence: 62%
“…NOBs were representing less than 0.1% (mostly Candidatus Nitrotoga arctica ) of the community. These results can explain the differences in the negative effect of antibiotics on nitrifying community between this study and previously reported data because of different key nitrifying bacteria …”
Section: Resultssupporting
confidence: 62%
“…These results suggest that electrochemistry-high resolution mass spectrometry is an interesting technique for studying oxidative reactions of organic compounds of environmental interest, as was previously suggested by Hoffmann et al [12]. Nitrifying bacteria in activated sludge [34].…”
Section: Thin-layer Flow Cell Coupled Online To High-resolution Mass supporting
confidence: 75%
“…In a previous study of the transformation of TRI under aerobic conditions in nitrifying activated sludge, this same structure was assigned to a transformation product of TRI with the same exact mass, albeit a completely different MS/MS spectrum [34]. While differences in MS/MS could be the result of different mass analyzers (the present study used an QqTOF while in the study of Jewell et al a linear ion trap-orbitrap mass spectrometer was used) mass accuracy, spectral accuracy and comparison of MS/MS spectrum and in silico fragmentation suggests that the most likely structure of OP290 is isomer E or (2,4-diaminopyrimidin-5-yl)-(4-hydroxy-3,5-dimethoxyphenyl)methanone.…”
Section: Electrochemically-assisted Fenton Reactionmentioning
confidence: 87%
“…However, previous reports on the effect of initial concentrations on biotransformation pathways of pharmaceuticals were contradictory. The same degradation route was reported on trimethoprim by nitrifying activated sludge with two metabolites produced at initial concentrations of 20 mg L -1 and 20 µg L -1 whereas different biotransformation products were found under different spiked concentration (500 µg L -1 and 5 µg L -1 ) in another study (Eichhorn et al, 2005;Jewell et al, 2016). This discrepancy might be due to the properties of the activated sludge and the dominant microorganisms in different studies, which deserve further research.…”
Section: This Section Summarises the Findings Of The Work Described Isupporting
confidence: 59%
“…Two metabolites were formed and the degradation route was independent on the initial concentration of trimethoprim (20 mg L -1 or 20 µg L -1 ). However, biodegradation of trimethoprim was also investigated by nitrifying activated sludge in another recent study (Jewell et al, 2016), resulting in different biotransformation products under different spiked concentration of trimethoprim (500 µg L -1 or 5 µg L -1 ). From the mass balance analysis, carboxy-acyclovir seems to be the only product by heterotrophs either in higher initial concentration or lower initial concentration of acyclovir.…”
Section: Discussionmentioning
confidence: 99%